2019
DOI: 10.1186/s12939-019-0963-9
|View full text |Cite
|
Sign up to set email alerts
|

Equity in healthcare financing: a case of Iran

Abstract: Background Fair financial contribution in healthcare financing is one of the main goals and challengeable subjects in the evaluation of world health system functions. This study aimed to investigate the equity in healthcare financing in Shiraz, Iran in 2018. Materials and methods This was a cross- sectional survey conducted on the Shiraz, Iran households. A sample of 740 households (2357 persons) was selected from 11 municipal districts using the multi-stage sampling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Unlike previous studies in Iran based on 1-year data [ 18 ] or for a single province [ 17 ], our study analyzed the equity in OOP payments for healthcare services and its catastrophic incidence using 6-year annual data points representing the whole Iran and also using WHO standard approach. The overall picture of the total, urban, and rural households’ OOP payments and the incidence of the CHE at different levels of the CTP over time shed light to understand the effectiveness of existing policies in the context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies in Iran based on 1-year data [ 18 ] or for a single province [ 17 ], our study analyzed the equity in OOP payments for healthcare services and its catastrophic incidence using 6-year annual data points representing the whole Iran and also using WHO standard approach. The overall picture of the total, urban, and rural households’ OOP payments and the incidence of the CHE at different levels of the CTP over time shed light to understand the effectiveness of existing policies in the context.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported a positive KPI and progressive OOP payments for healthcare for the urban residents and a negative KPI and regressive OOP for the rural ones [ 16 ]. Another study reported a negative (− 0.112) KPI for the healthcare costs (OOP payment for healthcare plus health insurance premiums) [ 17 ]. Besides, the KPI for general taxation and health insurance premiums were progressive and regressive, respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high inflationary effects of this policy [ 36 ], however, worsened the inequality in health care financing and made access to health care services more limited than before. Reducing the inequality in household OHP was considered auspicious in previous study [ 37 ], but the current study showed that high inequality in health spending was related to affluent families (households with insurance coverage and high-income households) in society. As a result, inequality should be interpreted cautiously in counties with high OHP shares in health care expenditures.…”
Section: Discussionmentioning
confidence: 69%
“…Indicators of inequality in health expenditures have been widely studied by Iranian researchers, but this study is the first to address the issue comprehensively over a 36-year timeframe [ 5 , 21 ]. Mehrolhassani et al [ 22 ] reported that the distribution of health care expenditures was unequal, especially in OHP, with the highest rate ranging from 0.50 to 0.59 during the study timeframe and the disparity index for OHP fluctuating between 37.01% and 65.85%.…”
Section: Introductionmentioning
confidence: 99%
“…According to the requirements of the fifth and sixth development plans of Iran to reduce out-of-pocket payments, increasing the government's share in financing public health expenses and appropriate allocation of public resources in the health sector is of great importance, and for this reason, providing fair health care services and accessible to the general public has been one of the concerns of the governments of the time and the realization of this goal has always faced serious challenges and obstacles [ 29 ]. The implementation of health system transformation plan in 2014 with the aim of reducing the costs of direct payment from the households' pockets, especially regarding treatment costs in the inpatient and hospital sectors, is considered as one of the important reforms in the Iran health financing system [ 26 ].…”
Section: Introductionmentioning
confidence: 99%